PWE-287 Breath volatile analysis for the recognition of harmful drinking, cirrhosis and hepatic encephalopathy. (28th May 2012) - Khalid, T Y; De Lacy Costello, B; Ewen, R; White, P; Stevens, S; Gordon, F; Collins, P; McCune, A; Shenoy, A; Shetty, S; Ratcliffe, N M; Probert, C S
Abstract : Introduction: Hepatic encephalopathy (HE) is a neuropsychiatric state which may complicate cirrhosis following the accumulation of toxic substances that cross the blood-brain barrier and affect brain function. Cirrhosis or portal-systemic shunting results in the accumulation of substances in the blood that may undergo alveolar gas exchange to be excreted in the breath. The aim of this work was to investigate the use of breath analysis as a non-invasive and simpler means of diagnosing HE, cirrhosis and harmful drinking. Methods: A bespoke breath-sampling device was used to sample one litre of breath through adsorbent tubes from patients with alcohol-related cirrhosis with (n=11) and without HE (n=23), non-alcoholic cirrhosis without HE (n=19), harmful drinkers without cirrhosis (n=7), inflammatory respiratory disease (n=18), and healthy controls (n=15). Compounds trapped on these tubes were released via thermal desorption and analysed by gas chromatography mass spectrometry for separation and detection. Multivariate discriminant analysis was used to identify volatile organic compounds to differentiate patients according to disease status and build models for disease classification. Results: Models based on the presence or absence of volatiles were tested in the patient groups. HE was correctly classified in 91.0% of patients with alcoholic cirrhosis. Patients with cirrhosis could be discriminated from those without cirrhosis with 100% accuracy in drinkers. In patients without clinical signs of HE, alcohol was correctly predicted as the underlying cause of cirrhosis in 82.6% of patients and non-alcoholic causes of cirrhosis were correctly determined in 84.2% of patients. Non-alcoholic cirrhosis, alcoholic cirrhosis, and harmful drinking could also be discriminated from healthy controls with a sensitivity of 89.5%, 97.1% and 100%, respectively. Conclusion: Breath volatiles can be used to aid the diagnosis of HE, cirrhosis, and harmful levels of drinking, therefore breath testing may offer a means to detect liver conditions non-invasively at earlier and more treatable stages. Competing interests: None declared.